Multifunctional protein nucleobindin 1 as a marker of vascular damage in systemic lupus erythematosus - A. O. Mikhailina; O. S. Kostareva; E. A. Aseeva; S. I. Glukhova; A. M. Lila; S. V. Tishchenko (Современная ревматология)
The search for new biomarkers for the early diagnosis of systemic lupus erythematosus (SLE) is a crucial task. Objective: a comparative study of concentrations of conservative protein nucleobindin 1 (NUCB1) in the blood serum of patients with SLE and healthy donors and assessment of correlation of NUCB1 level with clinical and serological manifestations of the disease.Material and methods. The study included 21 patients with SLE who fulfilled SLICC criteria and 23 healthy donors. SLEDAI-2K index was used to assess SLE activity. Organ damage was assessed using SLICC damage index. Standard laboratory markers of SLE were analyzed in all patients. Concentration of NUCB1 in blood serum was determined using the enzyme immunoassay method. Results and discussion. The group of SLE patients included 20 women and 1 man (median age 33 [27; 40] years, disease duration 5 [3; 10] years), mainly with high disease activity (median SLEDAI-2K 8.5 [6.0; 14.0]). Kidney involvement was found in 52% of cases (nephritis), involvement of joints – in 67% (arthritis), vessels – in 33%, skin – in 67%, pericarditis – in 29%, hematological abnormalities – in 71%, antinuclear factor – in 76% and antibodies against double-stranded DNA – in 71%. An increase in the mean NUCB1 level to 3881 ng/ml was found in the blood serum of SLE patients compared to the control group (2766 ng/ml; p=0.048). Correlations of NUCB1 levels with vascular damage (r=0.653; p<0.05) and pericarditis (r=-0.490; p<0.05) were found. Conclusion. Elevated NUCB1 levels in the blood serum of SLE patients may indicate involvement of this protein in autoimmune and apoptotic processes. The observed correlation of NUCB1 levels with vascular affection and pericarditis is the basis for further studies on the involvement of this protein in the development of various diseases, including SLE.